Preparation of przewalskinic acid A from salvianolic acid B using a crude enzyme from an Aspergillus oryzae strain. (1st May 2014) - Liu, Chunying; Jin, Yinghua; Yu, Hongshan; Sun, Changkai; Zhou, Shuiping; Zhu, Yonghong; Xu, Longquan; Yu, Chong; Jin, Fengxie
Abstract: Przewalskinic acid A is a rare, water-soluble, and highly biologically active ingredient found, thus far, only in the Salvia przewalskii Maxim herb; however, the content in S. przewalskii herb is very low. In order to obtain useful quantities of przewalskinic acid A, the biotransformatin of salvianolic acid B from Salvia miltiorrhiza root (danshen in Chinese) into przewalskinic acid A was studied using a crude enzyme produced from Aspergillus oryzae D30s strain. The crude enzyme from the A. oryzae strain hydrolyzed salvianolic acid B into przewalskinic acid A and danshensu. The preparation afforded 31.3 g przewalskinic acid A (91.0 % purity) and 13.1 g danshensu (95 % purity) from 75 g salvianolic acid B. The preparation of przewalskinic acid A was therefore very successful with a yield of over 86 %, but the yield of danshensu was only 33 %. The product przewalskinic acid A was identified using ultra-performance liquid chromatography–mass spectrometry (UPLC–MS) and NMR.